A perda das colónias portuguesas na Índia : enquadramentos noticiosos no Diário de Notícias e Jornal do Comércio = The loss of the portuguese colonies in India : news framing in the journals Diário de Notícias and Jornal do Comércio - Lima, Helena (2019)
The invasion of Goa by Indian forces on December 18th, 1961, put an end toPortuguese claims to territory and was the culmination of a growing number oftensions that were reported in some way by the Union press. The malaise in theIndian colony was also a theme in the Portuguese newspapers, and this paperpresents an analysis of the Diário de Notícias and Jornal do Comércio, publishedin December 1961. The news framing adopted several narrative strategies andspecific discursive approaches. In the journalistic field, professional practice usesthe reference to sources as a strategy of objectivity. However, in this case, thesystematic use of the agencies may imply the notion of previously treated and nondirect information, namely in the use of Lusitania and ANI as quasi-exclusivesources of information. The news hierarchy is another of the unavoidable framingprocesses, since the presence in the cover and the increasing volume of newsindicate the news-value of the theme or its devaluation.